2021
DOI: 10.3390/antibiotics10040354
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Identification of Different Species of the Genus Aeromonas by Whole-Genome Sequencing and Use of Their Species-Specific β-Lactamases as Phylogenetic Markers

Abstract: Some Aeromonas species, potentially pathogenic for humans, are known to express up to three different classes of chromosomal β-lactamases, which may become hyperproduced and cause treatment failure. The aim of this study was to assess the utility of these species-specific β-lactamase genes as phylogenetic markers using whole-genome sequencing data. Core-genome alignments were generated for 36 Aeromonas genomes from seven different species and scanned for antimicrobial resistance genes. Core-genome alignment co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…examined in this study could be that they intrinsically are encoded in the genomes. Despite so, suffice to point out that the MBL genes detected in this study have been reported from different bacteria species isolated from humans, animals, fish, chickens, mussel and the environments in different countries ( Maravić et al, 2013 ; Bottoni et al, 2015 ; Hilt et al, 2020 ; Ramsamy et al, 2020 ; Bertran et al, 2021 ; Wang Y. et al, 2021 ). Thus, it is likely that these AMR genes exist in other bacteria species in different aquatic environments and a wide range of host species in India.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…examined in this study could be that they intrinsically are encoded in the genomes. Despite so, suffice to point out that the MBL genes detected in this study have been reported from different bacteria species isolated from humans, animals, fish, chickens, mussel and the environments in different countries ( Maravić et al, 2013 ; Bottoni et al, 2015 ; Hilt et al, 2020 ; Ramsamy et al, 2020 ; Bertran et al, 2021 ; Wang Y. et al, 2021 ). Thus, it is likely that these AMR genes exist in other bacteria species in different aquatic environments and a wide range of host species in India.…”
Section: Discussionmentioning
confidence: 78%
“…from reservoir water in Singapore (Zhong et al, 2021), A. media in Nebraska watershed (Donner et al, 2022), A. salmonicida from Atlantic salmon (Salmo salar L) in Chile (Vásquez-Ponce et al, 2022), and pork processing plant in Spain (Cobo-Díaz et al, 2021). Similarly, bla OXA-724 has been detected from A. dhakensis isolated from humans in Spain (Bertran et al, 2021), A. hydrophila from pigs in South Africa (Ramsamy et al, 2021) as well as A. jandaei and A. hydrophila from chicken and , while in the present study it was found in A. hydrophila from carp and A. veronii from sardine from India. bla OXA-72 has been detected from Acinetobacter baumannii in humans where it has been associated with pneumonia, septic shock, and respiratory failure (Jia et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, in certain cases such associations may be established with sufficient confidence, such as for linking the cphA4 carbapenemase and the ampS β-lactamase genes detected in the carp intestinal microbiome with Aeromonas spp. [ 51 , 52 ], or the association of the bla ACI-1 β-lactamase gene (at 100% coverage and 100% identity) with the anaerobic coccus Acidaminococcus intestinii ( Acidaminococcaceae ) in the pig fecal microbiome [ 53 , 54 ] ( Supplementary Table S3 ). Moreover, BLASTN searches of metagenomic contigs in some further cases also yielded database hits with both the coverage and identity at >99% and coupled with a specific bacterial genus for the highest alignment scores.…”
Section: Discussionmentioning
confidence: 99%
“…strains highlighted the role of water as a vehicle for the dissemination of the qnrS -resistance determinants [ 74 ], similar to the environment of fish production in aquaculture. Indeed, two of the ARGs that were detected only in the carp intestine in the current study, cphA4 and ampS , are characteristic ARGs of Aeromonas spp., an important genus for fish-pathogenic bacteria [ 52 ].…”
Section: Discussionmentioning
confidence: 99%